Central Bank of Nigeria : 'limits of authority' - Central Bank of Nigeria (Abuja, Nigeria Central Bank of Nigeria, 2000)
This manual was written in order to give the top management [esp. the governor] more time to concentrate on policy issues and strategic functions. It details the powers and responsibilities of officers.
nmn, 25/03/19
Arch
Keywords: Limits of authority; Central Bank of Nigeria